2020
DOI: 10.1007/s10886-020-01213-2
|View full text |Cite
|
Sign up to set email alerts
|

Herbivory and Time Since Flowering Shape Floral Rewards and Pollinator-Pathogen Interactions

Abstract: Young for help with data collection and feedback, the UMass Amherst Quantitative Statistics Group for feedback on statistical analyses, Biobest (Ontario, Canada) for donating bumblebee colonies, and J. van Wyk and R. Malfi for providing constructive comments on the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 88 publications
0
6
0
Order By: Relevance
“…Reflecting this foraging preference, bees had lower survival when fed pollen from powdery mildew-inoculated plants grown in conventional compared with organic soil (figures 1 and 5). These results suggest that bees may detect powdery mildew-induced changes to pollen quality in plants grown in conventional soils [5,5961]. In conventional soils, powdery mildew likely affected unmeasured components of floral reward chemistry, display, or scent that ultimately influenced bee attraction and survival [33,62].…”
Section: Discussionmentioning
confidence: 99%
“…Reflecting this foraging preference, bees had lower survival when fed pollen from powdery mildew-inoculated plants grown in conventional compared with organic soil (figures 1 and 5). These results suggest that bees may detect powdery mildew-induced changes to pollen quality in plants grown in conventional soils [5,5961]. In conventional soils, powdery mildew likely affected unmeasured components of floral reward chemistry, display, or scent that ultimately influenced bee attraction and survival [33,62].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, often laboratory studies that use the gut sampling method use B. impatiens as a host (e.g. Anthony et al ., 2015; Giacomini et al ., 2018; Aguirre et al ., 2020; Fowler et al ., 2022), whereas, studies that use the faecal sampling method often use B. terrestris as a host (e.g. Schmid-Hempel et al ., 1999; Logan et al ., 2005; Yourth and Schmid-Hempel, 2006; Folly et al ., 2020) (see Table S2).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies use different methods to count C. bombi cells, which may also affect infection estimates. For example, some studies count ‘live’ or ‘actively moving’ C. bombi cells (LoCascio, Pasquale, et al ., 2019 b ; Aguirre et al ., 2020). The criteria for which cells are being counted are not explicitly specified in these studies, but ‘live’ or ‘actively moving’ likely refers to only 2 of the cell types of this parasite (choanomastigote and promastigote, both of which have flagella and swim actively).…”
Section: Discussionmentioning
confidence: 99%
“…For example, secondary metabolites in floral rewards can be detrimental to bees [23,24], but some compounds in nectar can also reduce infections of C. bombi in bumblebees [25]. Studies thus far have found no clear relationships between pollen secondary metabolites and pathogen infections [26][27][28], but further research is needed. Overall, the role of dietary nutrients in bee immune function is key to understanding the influence of bee diet on pathogen infection.…”
Section: Introductionmentioning
confidence: 99%